Pengaruh Perhatian Orang Tua terhadap Tilawah Qur’an Peserta Didik di SMKN 40 Jakarta Timur - Muhammad Nagib; Ishak Syairozi (Departement of Mathematics Education, 2024)
The study was undermined by the findings of symptoms of decreased reading of the Qur'an by pupils due to less attention from older people. The child does not follow tadarus on the grounds that there are religious lessons in his school, as well as the influence of internal and external factors, for which research is intended to reveal the role of the attention of the parents to the Qur'an of the pupils. This research aims to find out the influence of the attention of the parents in SMK N 40 East Jakarta on developing a good Koran Tilawah. The hypothesis that the researchers have proposed is Ha: There is an influence of the attention of the elderly on the revelations of the Qur'an of the students of SMK N 40 East Jakarta. The method used in this study is the method of quantitative correlation. Using a simple random sampling method, 35 students of SMK N 40 Jakarta were equipped with data collection and observation techniques. In analyzing using product moment correlation techniques, The results of the study show that, if seen from the test coefficient, the product moment yields “rxy” or “ro” of 0.409, whereas “rt” in the table is significant at 5% = 0.339 and the degree is significant at 1% = 0.436. Thus, it can be known that